The Prevention of Suicide in Older Military Veterans - Joshua Levine; Leo Sher (Behavioral Sciences)
Suicidal behavior among older military veterans is an important medical and social problem. The goal of this literature review is to discuss this underappreciated issue and identify suicide preventive interventions that can be utilized with the older military veteran population. Older veterans experience psychiatric, medical, and social problems associated with their age and/or military experience that can contribute to suicide risk. These problems include relationship losses through death or estrangement, depression, cognitive decline, loneliness, isolation, frailty, mobility issues, and chronic pain. Therefore, older veterans face a unique set of challenges. Suicide prevention in older veterans should take a multipronged approach which includes screening for suicidality, management of psychiatric and medical disorders, social assistance, safety planning, lethal means restriction, and involving family members in the veteran’s healthcare. Family members should be included in the safety planning process when possible. Gatekeeper training programs can be utilized to train individuals who are working with older veterans to reduce suicides amongst this age group.